Pengaruh Video Animasi sebagai Media Pembelajaran dalam Meningkatkan Keterampilan Mengajar di Sekolah Dasar - Maemunah; Desty Endrawati Subroto; Indah Febriyanti; Siti Fattimah; Faren Aulia Meilani; Ilham Mubarok (Universitas Serambi Mekkah, 2025)
This study aims to investigate the impact of using animated videos in the teaching process on improving students' teaching skills at the elementary school level. This study used a quantitative method involving 50 students from SDN Purwadadi 2. Data were collected through distributing questionnaires covering various indicators of teaching skills, such as classroom management, explaining materials, maintaining students' attention, student participation in the learning process, and teachers' ability to convey information. The results of this study indicate that the use of animated videos has a positive and significant effect on students' learning abilities, especially in terms of understanding the material, so that it becomes more effective, improves, and makes difficult concepts easier to digest through visualization, which also increases students' enthusiasm and activity, and makes learning more diverse and interesting through animated media. Based on the information presented in the diagram, teacher skill improvement was seen significantly in five indicators of teaching ability, which can be seen from the posttest score which is higher than the pretest. The average increase for each indicator showed a fairly significant difference in value, ranging from 20 to 24 points, indicating consistent and positive development in all aspects of teaching skills. The indicator with the highest increase was student engagement in the learning process, which showed the greatest increase, namely 24 points (from 62 to 86), while the indicator with the lowest increase was classroom management skills, which only increased by 20 points (from 65 to 85), although it still showed good progress. This study provides evidence that animated videos can function as an effective learning tool at the elementary school level